KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 UNTUK MENINGKATKAN MUTU SEKOLAH - Fitriyah, Idatul; Santosa, Achadi Budi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2020)
Improving the quality of education is an orientation of the development of national civilization as an investment in the future development. Especially now entering the era of the industrial revolution, of course, the quality of schools needs to be improved. The principal's leadership is needed to deal with this era, because the principal is a leader who means the school and is a person who has authority in the school. The ideal leadership is leadership that follows the demands of the industrial revolution 4.0. Leaders who follow the development of technology leaders must have skills in influencing, encouraging, guiding, directing, and moving others who have something to do with the implementation and development of education and teaching in the era of the industrial revolution 4.0. The purpose of this study is to determine the leadership of school principals in the face of changing times, especially in era 4.0 and explain the study of leadership concepts in dealing with era 4.0. The method used is a qualitative method. The results of the discussion can be concluded that the principal's leadership must be able to master in the field of technology needed as currently in the era of the digital revolution 4.0 to improve and explore the potential that exists in itself and the need for the readiness of the principal in facing challenges in the era of the digital revolution 4.0.